The association between physical activity and cognitive function in the elderly in rural areas of northern China - Wang, Xueyan; Zhang, Jiesong; Chen, Chen; Lu, Zhonghai; Zhang, Dongfeng; Li, Suyun (Frontiers in Aging Neuroscience, 2023)
Background: Physical activity plays an important role in cognitive function in older adults, and the threshold effect and saturation effect between physical activity and cognitive function are unclear. Objective: The purpose of this study was to explore the threshold effect and saturation effect between physical activity and cognitive function in the elderly. Methods: The International Physical Activity Questionnaire (IPAQ) was used to measure moderate-intensity physical activity and vigorous-intensity physical activity and total physical activity in older adults. Cognitive function assessment uses the Beijing version of the Montreal Cognitive Assessment Scale (MoCA). The scale consists of 7 parts: visual space, naming, attention, language, abstract ability, delayed recall and orientation, for a total of 30 points. The total score of the study participants < 26 was defined as the optimum cutoff point for a definition of mild cognitive impairment (MCI). The multivariable linear regression model was used to initially explore the relationship between physical activity and total cognitive function scores. The logistic regression model was used to assess the relationship between physical activity and cognitive function dimensions and MCI. The threshold effect and saturation effect between the total physical activity and the total cognitive function scores were investigated by smoothed curve fitting. Results: This cross-sectional survey had a total of 647 participants aged 60 years and older (mean age: 73years, female: 53.7%). Participants’ higher level of physical activity were associated with higher visual space, attention, language, abstract ability, and delayed recall scores (P < 0.05). Physical activity was not statistically associated with naming and orientation. Physical activity was a protective factor for MCI (P < 0.05). Physical activity was positively correlated with total cognitive function scores. There was a saturation effect between total physical activity and total cognitive function scores, and the saturation point was 6546 MET * min/ wk. Conclusion: This study showed a saturation effect between physical activity and cognitive function, and determined an optimal level of physical activity to protect cognitive function. This finding will help update physical activity guidelines based on cognitive function in the elderly.